2016
DOI: 10.1016/j.redox.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and L-carnitin improves endothelial disfunction and oxidative stress in Type 2 diabetic rats

Abstract: Vascular dysfunction is thought to play a major role in the development of diabetic cardiovascular disease. The roles of endothelial dysfunction, oxidative stress, and dyslipidemia will be considered. Melatonin as well as L-carnitine were shown to possess strong antioxidant properties. Diabetes induced with high fat diet (for 8 weeks) and multipl low doses intraperitoneal injection of STZ (twice, 30 mg/kg/d i.p). The diabetic animals were randomly assigned to one of the experimental groups as follows: Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 21 publications
3
59
0
1
Order By: Relevance
“…Intraperitoneal administration of 600 mg/kg/ day of L-carnitine attenuated serum glucose, and lipid profile in a rat model of type 2 diabetes [27]. Previous ly, we showed that 600 mg/kg/day of oral L-carnitine administration (5 weeks) reduced serum glucose and normalized insulin in STZ-induced diabetic rats [15].…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Intraperitoneal administration of 600 mg/kg/ day of L-carnitine attenuated serum glucose, and lipid profile in a rat model of type 2 diabetes [27]. Previous ly, we showed that 600 mg/kg/day of oral L-carnitine administration (5 weeks) reduced serum glucose and normalized insulin in STZ-induced diabetic rats [15].…”
Section: Resultsmentioning
confidence: 60%
“…Previous ly, we showed that 600 mg/kg/day of oral L-carnitine administration (5 weeks) reduced serum glucose and normalized insulin in STZ-induced diabetic rats [15]. Other studies also evaluated the therapeutic effects of L-carnitine in diabetic models [15,27,28]. We found that high doses of L-carnitine (200 and 300 mg/kg/day; i.p.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Melatonin (N-acetyl-5-methoxytryptamine) hormone is mainly secreted by pineal gland and most of physiological functions in the body are affected by the hormone (Ekmekcioglu, 2006;Sharafati-Chaleshtori et al, 2017). A main role of the hormone in the body is antioxidant role and evidences from studies proved a key role of melatonin in the ROS production through regulation of glucose metabolism in the pathogenesis of diabetes (Salmanoglu et al, 2016;Kahya et al, 2017). Positive role of melatonin on blood antioxidants levels such as reduced glutathione (GSH) level and glutathione peroxidase (GPx) activity in several diseases except diabetes was reported (Urata et al, 1999;Reiter et al, 2001).…”
Section: List Of Abbreviations;mentioning
confidence: 98%
“…L-carnitine (β-hydroxy-γ-N-trimethylaminobutyric acid; LC), the biologically active form of carnitine, is an amino acid-like agent involved in the transit of long chain fatty acids that is synthesized in various tissues (7) and serves an impor-and serves an important role in fatty acid oxidation (8). Bach et al (9) reported that the skeletal muscle, heart, intestines, testis and in particular liver, can hydroxylate γ-butyrobetaine into carnitine.…”
Section: Introductionmentioning
confidence: 99%